Helium ion beam imaging for image guided ion radiotherapy - Martišíková, Mária; Gehrke, Tim; Berke, S.; Aricó, Giulia; Jäkel, Oliver (Radiation oncology, 2018)
Ion beam radiotherapy provides potential for increased dose conformation to the target volume. To translate it into a clinical advantage, it is necessary to guarantee a precise alignment of the actual internal patient geometry with the treatment beam. This is in particular challenging for inter- and intrafractional variations, including movement. Ion beams have the potential for a high sensitivity imaging of the patient geometry. However, the research on suitable imaging methods is not conclusive yet. Here we summarize the research activities within the “Clinical research group heavy ion therapy” funded by the DFG (KFO214). Our aim was to develop a method for the visualization of a 1 mm thickness difference with a spatial resolution of about 1 mm at clinically applicable doses.